Identification of the Histone Deacetylases Gene Family in Hemp Reveals Genes Regulating Cannabinoids Synthesis - Yang, Liu; Meng, Xiangxiao; Chen, Shilin; Li, Jun; Sun, Wei; Chen, Weiqiang; Wang, Sifan; Wan, Huihua; Qian, Guangtao; Yi, Xiaozhe; Li, Juncan; Zheng, Yaqin; et al. (Frontiers in Plant Science, 2021)
Abstract Histone deacetylases (HDACs) play crucial roles nearly in all aspects of plant biology, including stress responses, development and growth, and regulation of secondary metabolite biosynthesis. The molecular functions of HDACs have been explored in depth in Arabidopsis thaliana, while little research has been reported in the medicinal plant Cannabis sativa L. Here, we excavated 14 CsHDAC genes of C. sativa.L, which were divided into three relatively conserved subfamilies, including RPD3/HDA1 (10 genes), SIR2 (2 genes) and HD2 (2 genes). Genes that associated with the biosynthesis of bioactive constituents were identified by combining the distribution of cannabinoids with the expression pattern of HDAC genes in various organs. Using qRT-PCR and transcription group analysis, we verified the expression of candidate genes in different tissues. We found that the histone inhibitor Trichostatin A (TSA) had an effect on the expression of key genes in the cannabinoid metabolism pathway and the accumulation of synthetic precursors, which indirectly indicates that histone inhibitor may regulate the synthesis of active substances in Cannabis sativa L.